Antifungal and Antimicrobial Activities of New Schiff Base and Its Metal Complexes - Toroglu, Sevil; Ispir, Esin; ÇELIK, Cumali (Asian Journal of Chemistry, 2010)
The in vitro antibacterial and antifungal activities of Schiff base derived from the reaction of phthaldehyde with 4-amino-2,3-dimethyl-1- phenyl-3-pyrozolin-5-one and its Co(II), Cu(II) and Ni(II) metal complexes were investigated. The structure of the Schiff base was confirmed by 1H NMR. Schiff base and its metal complexes were evaluated for both their in vitro antibacterial activity against Klebsiella pneumoniae FMC 5, Enterococcus cloacae ATCC 13047, Escherichia coli ATCC 8739, Bacillus megaterium DSM 32, Staphylococcus aureus Cowan 1, Micrococcus luteus LA 2971, Mycobacterium smegmatis CCM 2067, Pseudomonas aeruginosa ATCC 27853 and their in vitro antifungal activity against Candida albicans ATCC 1023, Kluyveromyces fragilis A 230, Rhodotorula rubra by the disc diffusion method. The antimicrobial activities tended to decrease with the increasing size of the amino acid residues.